Seeing and living like a cross-border pastoralist : local struggles over state resources and services on the Uganda-DRC border - Nuwamanya, Alfred Katabyama (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.